Duodenal ulcer perforation and its consequences - Malik, Mariam; Magsi, Abdul Malik; Parveen, Sughra; Khan, Muhammad Iqbal; Iqbal, Mazhar (Journal of the Pakistan Medical Association, 2023)
Duodenal ulcer perforation, a frequent surgical emergency, needs simple closure with indirect Graham’s Omentopexy which is effective with excellent results in majority of cases despite patients’ late presentation. The objective of the study was to determine the frequency of postoperative complications of perforated duodenal ulcer, conducted in the Surgery Department, Jinnah Postgraduate Medical Centre, Karachi, from March 20, 2018 to September 20, 2018. The study was a descriptive case series of 108 patients of both genders with perforated duodenal ulcer > 1 week old with ASA score I & II. Patients with trauma and co-morbidities were excluded. The patients underwent laparotomy and peritoneal toilet, and after noting the site of perforation indirect Graham’s Omentopexy was performed. Complications like duodenal fistula, peritonitis, and paralytic ileus, and patient’s death within 10 days of surgery were noted. —Continue